Perceptions of Afghan EFL undergraduate learners towards autonomous learning - Hashmatullah Tareen; BaoHui Zhang; Mohammad Tahir Haand (Asian-Pacific Journal of Second and Foreign Language Education, 2024)
Abstract Autonomous learning is extensively acknowledged as a desirable goal in undergraduate education as it is found to comply with learner-centered approaches and enable learners to pursue life-long learning. However, very few empirical researchers have closely examined the actual practices of autonomous learning in the Afghan context. Therefore, the main purpose of the current research project was to investigate EFL undergraduates’ perceptions of autonomous learning, strategies used for improving language proficiency, and the extent to of these strategies are deployed. With regard to achieving these objectives, a mixed-method approach was adopted. The quantitative data were analyzed through SPSS v24 by conducting descriptive and inferential statistics. The findings revealed that EFL learners had positive perspectives on autonomous learning and were ready to take the initiative in autonomous learning. Qualitative analysis of nine EFL students’ interviews revealed that they have to create learning goals for their learning, assess themselves for controlling their learning, and take part in inside and outside classroom activities to improve their language proficiency. This case study concludes that the findings cannot be generalized to other contexts, and the study makes an original contribution to understanding the promotion of autonomous learning at Kandahar University. In addition, this study offers practical implications for policymakers and lecturers who are interested in adopting autonomous learning as a worthwhile educational goal.